Planning and monitoring of sports training: What is it and how to teach it? - Roy, M.; Roy, X.; Chevrier, J.; Cardinal, C. H. (LASE Journal of Sport Science, 2018)
Planning training is an important sport coaching topic. It is frequently taught in large-scale education programs targeting coaches with various profiles and experience. However, there are different ways of delivering planning training, and there is a need to question the content and teaching methods used in workshops that offer education on this topic. The objectives of this article are (a) to present definitions and models related to planning and monitoring training, (b) to present the results of a case study on coaches` experience while participating in workshops that teach planning training, and (c) to reflect on an approach to teaching planning training that is based on reflective practice and critical thinking. The participants were thirteen coaches who attended workshops on planning training. Interviews were conducted with each coach before and after their respective workshops. These coaches also created training plans before and after their workshops, and these were analysed to understand what coaches had learned and what modifications have been brought to their plan. Overall, the workshops were evaluated as being useful, for various reasons. It was difficult to determine precisely what the coaches have learned during the workshops. Results confirmed the conclusions of many authors about the impact of large-scale coach education programs: education on planning training should be tailored on the coaches` profiles and needs, and this education should follow a socioconstructivist approach, emphasizing an experiential and reflective approach.